Intermittent hypoxic training – derived exosomes in stroke rehabilitation - Ryou, Myoung-Gwi; Burton, Summer (Frontiers in Integrative Neuroscience, 2024)
Ischemic stroke is the fourth leading cause of adult disability in the US, and it is a huge social burden all over the world. However, the efficient treatment of ischemic stroke is not available. An apparent reason for failing to find or develop an intervention for ischemic stroke is contributed to the tight blood–brain barrier (BBB). The unique characteristics of exosomes that can traverse BBB have been highlighted among researchers investigating interventions for ischemic stroke conditions. Additionally, intermittent hypoxic training has been considered a potential intervention in the treatment or rehabilitation process of ischemic stroke patients. In this mini-review, we are going to review the possibility of applying exosomes produced by a subject who does intermittent hypoxic conditioning in a treatment program for ischemic stroke.